Low-creep PP composite material for buckle and preparation method of low-creep PP composite material
By adding modified carbon nanotubes and modified additives to the PP material, the problem of poor creep resistance effect of PP material is solved, and the service life and safety of the buckle are significantly improved.
Patent Information
- Application Number
- CN202411988421.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
At this stage, PP materials have poor creep resistance, resulting in a short service life of the snap, affecting the safety of use.
Modified carbon nanotubes were prepared by hydrolyzing the carbon nanotubes with 3-mercaptopropyltrimethoxysilane to form functionalized carbon nanotubes and reacting with 4-vinylbenzaldehyde under light conditions. Then, the modified carbon nanotubes, modified additives and other raw materials are melt-blended in a mixer to obtain a low-creep PP composite material for snapping.
It improves the creep resistance and impact resistance of PP composite materials, extends the service life of the snap, and enhances the safety of use.
Smart Images

Figure BDA0005223110340000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PP composite material preparation, and in particular to a low creep PP composite material for buckles and a preparation method thereof. Background Art
[0002] A clip is a mechanism used to connect and fix different parts. The choice of material depends on the specific application requirements and includes: plastic clips, metal clips, elastic clips and nut and bolt clips. Plastic clips are favored by people for their advantages such as light weight, easy processing and installation. Commonly used materials for plastic clips are polypropylene and polycarbonate. Polypropylene has high durability and stability and becomes the preferred material. However, polypropylene has a semi-crystalline molecular form, a long and relatively flexible molecular chain. Under the action of long-term fatigue stress, the material is prone to creep, resulting in deformation of parts and even high-risk failure, which seriously affects safety of use. Summary of the invention
[0003] The object of the present invention is to provide a low creep PP composite material for buckles and a preparation method thereof, so as to solve the problem that the anti-creep effect of PP materials at present is poor, resulting in a short service life of the buckles.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a low creep PP composite material for a buckle, specifically comprising the following steps:
[0006] Step A1: dispersing carbon nanotubes in ethanol, stirring and adding 3-mercaptopropyltrimethoxysilane and deionized water at a speed of 200-300 r / min and a temperature of 60-70° C., reacting for 3-5 hours to obtain functionalized carbon nanotubes, and uniformly mixing the functionalized carbon nanotubes, 4-vinylbenzaldehyde, benzophenone and toluene, reacting for 20-30 minutes under 365 nm ultraviolet light irradiation to obtain modified carbon nanotubes;
[0007] Step A2: Weigh the following raw materials in parts by weight: 100-120 parts of PP masterbatch, 5-10 parts of modified additives, 5-8 parts of modified carbon nanotubes, 0.5-0.8 parts of diisopropyl peroxide and 0.1-0.3 parts of tetraisopropyl titanate, add the PP masterbatch, modified additives and diisopropyl peroxide into an internal mixer, melt blend for 5-10 minutes at a speed of 50 r / min and a temperature of 190-195°C, then add the modified carbon nanotubes and tetraisopropyl titanate, and melt blend for 20-30 minutes to obtain a low creep PP composite material for buckles.
[0008] Furthermore, the amount of 3-mercaptopropyltrimethoxysilane used in step A1 is 3% of the mass of the carbon nanotubes, the molar ratio of the mercapto groups on the functionalized carbon nanotubes to 4-vinylbenzaldehyde is 1:1, and the amount of benzophenone used is 1% of the mass of 4-vinylbenzaldehyde.
[0009] Further, the modified additive is prepared by the following steps:
[0010] Step B1: Tetramethyltetrasiloxane, p-nitrostyrene, chloroplatinic acid and DMF are mixed evenly, and reacted for 3-5 hours at a speed of 120-150 r / min and a temperature of 70-80° C. to obtain a modified monomer; trimethylsilane, n-butyl lithium and hexane are mixed evenly, and nitrogen is introduced for protection, and stirred for 1-1.5 hours at a speed of 60-80 r / min and a temperature of 10-15° C., and the temperature is raised to 40-50° C., hexamethylcyclotrisiloxane, the modified monomer and tetrahydrofuran are added, and the reaction is carried out for 2-3 hours, and the temperature is lowered to 20-25° C., dimethylchlorosilane is added, and the reaction is carried out for 10-15 hours to obtain a monohydrogen-terminated polysiloxane;
[0011] Step B2: uniformly mix monohydrogen-terminated polysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF, and react for 3-5 hours at a speed of 120-150 r / min and a temperature of 70-80° C. to obtain a modifier; uniformly mix octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and react for 2-3 hours at a speed of 150-200 r / min and a temperature of 105-110° C. to obtain a diamine-terminated polysiloxane; uniformly mix the diamine-terminated polysiloxane, the modifier and DMF, and react for 3-5 hours at a speed of 200-300 r / min, a temperature of 30-40° C. and a pH of 11-12 to obtain a functionalized polysiloxane;
[0012] Step B3: Mix the functionalized polysiloxane, triethylamine and DMF evenly, stir and add acryloyl chloride at a speed of 200-300 r / min and a temperature of 20-25°C, and react for 2-3 hours to obtain vinyl polysiloxane; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add vinyl polysiloxane at a speed of 150-200 r / min and a temperature of 80-85°C, and react for 3-5 hours to obtain a modified additive.
[0013] Furthermore, the molar ratio of tetramethyltetrasiloxane and p-nitrostyrene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrasiloxane, and the amount ratio of trimethylsilane, n-butyl lithium, hexane, hexamethylcyclotrisiloxane, modified monomer, tetrahydrofuran and dimethylchlorosilane is 1mmo l:1mmo l:10mmo l:10mmo l:5mmo l:20mL:2mmo l.
[0014] Furthermore, the molar ratio of the monohydrogen-terminated polysiloxane and allyl alcohol glycidyl ether described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of the monohydrogen-terminated polysiloxane, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 2.4:2:3, and the molar ratio of the diamine-terminated polysiloxane and the modifier is 1:4.
[0015] Furthermore, the molar ratio of the functionalized polysiloxane, triethylamine and acryloyl chloride described in step B3 is 1:4.1:4, and the usage ratio of zinc powder, ammonium chloride, deionized water, DMF and vinyl polysiloxane is 3g:1.5g:20mL:50mL:2g.
[0016] Beneficial effects of the present invention: A low creep PP composite material for a buckle disclosed by the present invention comprises the following raw materials: PP masterbatch, a modified additive, modified carbon nanotubes, diisopropyl peroxide and tetraisopropyl titanate; the modified carbon nanotubes are hydrolyzed with carbon nanotubes and 3-mercaptopropyltrimethoxysilane as raw materials, so that the siloxane on the 3-mercaptopropyltrimethoxysilane is hydrolyzed into silanol and grafted with the hydroxyl group on the surface of the carbon nanotube to obtain functionalized carbon nanotubes; the functionalized carbon nanotubes and 4-vinylbenzaldehyde are reacted under light conditions, so that the mercapto group on the functionalized carbon nanotubes and the double bond on the 4-vinylbenzaldehyde are grafted to obtain the modified carbon nanotubes.
[0017] The modified additive is made of tetramethyltetrasiloxane and p-nitrostyrene as raw materials. Under the action of chloroplatinic acid, the Si-H bond on the tetramethyltetrasiloxane reacts with the double bond on the p-nitrostyrene to obtain a modified monomer. Trimethylsilane and n-butyl lithium are reacted to form trimethylsilanol lithium, which is subjected to anionic ring-opening polymerization with hexamethylcyclotrisiloxane and the modified monomer, and then the reaction is terminated by end-capping with dimethylchlorosilane to obtain a monohydrogen-terminated polysiloxane. The monohydrogen-terminated polysiloxane is reacted with allyl alcohol glycidyl ether, so that the Si-H bond on the monohydrogen-terminated polysiloxane reacts with the double bond on the allyl alcohol glycidyl ether to obtain a modifier. Octamethylcyclotetrasiloxane is ring-opened and then reacted with 1,3-di(3 -aminopropyl)tetramethyldisiloxane is polymerized to form a diamine-terminated polysiloxane, the diamine-terminated polysiloxane is reacted with a modifier so that the amino group on the diamine-terminated polysiloxane reacts with the epoxy group on the modifier to form a new hydroxyl group to obtain a functionalized polysiloxane, the functionalized polysiloxane is reacted with acryloyl chloride so that the hydroxyl group on the functionalized polysiloxane reacts with the acyl chloride on the acryloyl chloride to obtain a vinyl polysiloxane, the vinyl polysiloxane is reduced with zinc powder so that the nitro group on the vinyl polysiloxane is converted into an amino group to obtain a modified additive.
[0018] When PP masterbatch, modified additives and diisopropyl peroxide are melt blended, diisopropyl peroxide generates free radicals, which can attack carbon atoms on the polypropylene molecular chain, thereby interrupting the linear structure of the polypropylene molecular chain. The ends of the interrupted molecular chains carry free radicals, which can recombine with the unsaturated double bonds on the modified additive molecules to form a cross-linked grid structure, thereby reducing the slip of the molecular chain. The benzene ring structure contained in the modified additive molecules can increase the rigidity, thereby improving the creep resistance of the composite material. Modified carbon nanotubes and tetraisopropyl titanate are added to continue melt blending. The aldehyde groups on the modified carbon nanotubes react with the amino groups on the side chains of the modified additives to form imine bonds, thereby forming a reversible cross-linked network of imine bonds in the composite material, thereby improving the impact resistance of the material. The addition of modified carbon nanotubes further limits the slip of the molecular chain, and can act as a nucleating agent to promote polymer crystallization, forming a more complete and fine crystal structure, and better resisting the slip of the molecular chain. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Embodiment 1: A method for preparing a low creep PP composite material for buckles, comprising the following steps:
[0021] Step A1: dispersing carbon nanotubes in ethanol, stirring and adding 3-mercaptopropyltrimethoxysilane and deionized water at a speed of 200 r / min and a temperature of 60° C., and reacting for 3 hours to obtain functionalized carbon nanotubes; mixing the functionalized carbon nanotubes, 4-vinylbenzaldehyde, benzophenone and toluene uniformly, and reacting for 20 minutes under the condition of 365 nm ultraviolet light irradiation to obtain modified carbon nanotubes;
[0022] Step A2: Weigh the following raw materials in parts by weight: 100 parts of PP masterbatch, 5 parts of modified additives, 5 parts of modified carbon nanotubes, 0.5 parts of diisopropyl peroxide and 0.1 parts of tetraisopropyl titanate, add the PP masterbatch, modified additives and diisopropyl peroxide into an internal mixer, melt blend for 5 minutes at a speed of 50 r / min and a temperature of 190°C, then add the modified carbon nanotubes and tetraisopropyl titanate, melt blend for 20 minutes to obtain a low creep PP composite material for buckles.
[0023] The amount of 3-mercaptopropyltrimethoxysilane used in step A1 is 3% of the mass of the carbon nanotubes, the molar ratio of the mercapto groups on the functionalized carbon nanotubes to 4-vinylbenzaldehyde is 1:1, and the amount of benzophenone used is 1% of the mass of 4-vinylbenzaldehyde.
[0024] The model of the PP masterbatch described in step A2 is HP501 M.
[0025] The modified additive is prepared by the following steps:
[0026] Step B1: Tetramethyltetrasiloxane, p-nitrostyrene, chloroplatinic acid and DMF are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 70° C. for 3 h to obtain a modified monomer; trimethylsilane, n-butyl lithium and hexane are mixed evenly, and nitrogen is introduced for protection, and stirred for 1 h at a speed of 60 r / min and a temperature of 10° C., and the temperature is raised to 40° C., hexamethylcyclotrisiloxane, the modified monomer and tetrahydrofuran are added, and the reaction is carried out for 2 h, and the temperature is lowered to 20° C., dimethylchlorosilane is added, and the reaction is carried out for 10 h to obtain a monohydrogen-terminated polysiloxane;
[0027] Step B2: uniformly mix monohydrogen-terminated polysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF, and react at a speed of 120 r / min and a temperature of 70° C. for 3 h to obtain a modifier; uniformly mix octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and react at a speed of 150 r / min and a temperature of 105° C. for 2 h to obtain a diamine-terminated polysiloxane; uniformly mix the diamine-terminated polysiloxane, the modifier and DMF, and react at a speed of 200 r / min, a temperature of 30° C. and a pH value of 11 for 3 h to obtain a functionalized polysiloxane;
[0028] Step B3: Mix the functionalized polysiloxane, triethylamine and DMF evenly, stir and add acryloyl chloride at a speed of 200 r / min and a temperature of 20°C, and react for 2 hours to obtain vinyl polysiloxane; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add vinyl polysiloxane at a speed of 150 r / min and a temperature of 80°C, and react for 3 hours to obtain a modified additive.
[0029] The molar ratio of tetramethyltetrasiloxane and p-nitrostyrene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrasiloxane, and the amount ratio of trimethylsilane, n-butyl lithium, hexane, hexamethylcyclotrisiloxane, modified monomer, tetrahydrofuran and dimethylchlorosilane is 1mmo l:1mmo l:10mmo l:10mmo l:5mmo l:20mL:2mmol.
[0030] The molar ratio of the monohydrogen-terminated polysiloxane and allyl alcohol glycidyl ether described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of the monohydrogen-terminated polysiloxane, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 2.4:2:3, and the molar ratio of the diamine-terminated polysiloxane and the modifier is 1:4.
[0031] The molar ratio of the functionalized polysiloxane, triethylamine and acryloyl chloride described in step B3 is 1:4.1:4, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and vinyl polysiloxane is 3g:1.5g:20mL:50mL:2g.
[0032] Embodiment 2: A method for preparing a low creep PP composite material for buckles, comprising the following steps:
[0033] Step A1: dispersing carbon nanotubes in ethanol, stirring and adding 3-mercaptopropyltrimethoxysilane and deionized water at a speed of 200 r / min and a temperature of 65° C., and reacting for 4 hours to obtain functionalized carbon nanotubes; mixing the functionalized carbon nanotubes, 4-vinylbenzaldehyde, benzophenone and toluene uniformly, and reacting for 25 minutes under 365 nm ultraviolet light irradiation to obtain modified carbon nanotubes;
[0034] Step A2: Weigh the following raw materials in parts by weight: 110 parts of PP masterbatch, 8 parts of modifying additives, 6.5 parts of modified carbon nanotubes, 0.6 parts of diisopropyl peroxide and 0.2 parts of tetraisopropyl titanate, add the PP masterbatch, modifying additives and diisopropyl peroxide into an internal mixer, melt blend for 10 minutes at a speed of 50 r / min and a temperature of 190°C, then add the modified carbon nanotubes and tetraisopropyl titanate, and melt blend for 25 minutes to obtain a low creep PP composite material for buckles.
[0035] The amount of 3-mercaptopropyltrimethoxysilane used in step A1 is 3% of the mass of the carbon nanotubes, the molar ratio of the mercapto groups on the functionalized carbon nanotubes to 4-vinylbenzaldehyde is 1:1, and the amount of benzophenone used is 1% of the mass of 4-vinylbenzaldehyde.
[0036] The model of the PP masterbatch described in step A2 is HP501 M.
[0037] The modified additive is prepared by the following steps:
[0038] Step B1: Tetramethyltetrasiloxane, p-nitrostyrene, chloroplatinic acid and DMF are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 75° C. for 4 hours to obtain a modified monomer; trimethylsilane, n-butyl lithium and hexane are mixed evenly, and nitrogen is introduced for protection, and stirred for 1 hour at a speed of 60 r / min and a temperature of 15° C., and the temperature is raised to 45° C., hexamethylcyclotrisiloxane, the modified monomer and tetrahydrofuran are added, and the reaction is carried out for 2 hours, and the temperature is lowered to 25° C., dimethylchlorosilane is added, and the reaction is carried out for 13 hours to obtain a monohydrogen-terminated polysiloxane;
[0039] Step B2: uniformly mix monohydrogen-terminated polysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF, and react at a speed of 120 r / min and a temperature of 75° C. for 4 h to obtain a modifier; uniformly mix octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and react at a speed of 150 r / min and a temperature of 110° C. for 2 h to obtain a diamine-terminated polysiloxane; uniformly mix the diamine-terminated polysiloxane, the modifier and DMF, and react at a speed of 200 r / min, a temperature of 35° C. and a pH of 12 for 4 h to obtain a functionalized polysiloxane;
[0040] Step B3: Mix the functionalized polysiloxane, triethylamine and DMF evenly, stir and add acryloyl chloride at a speed of 200 r / min and a temperature of 25°C, and react for 2 hours to obtain vinyl polysiloxane; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add vinyl polysiloxane at a speed of 200 r / min and a temperature of 80°C, and react for 4 hours to obtain a modified additive.
[0041] The molar ratio of tetramethyltetrasiloxane and p-nitrostyrene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrasiloxane, and the amount ratio of trimethylsilane, n-butyl lithium, hexane, hexamethylcyclotrisiloxane, modified monomer, tetrahydrofuran and dimethylchlorosilane is 1mmo l:1mmo l:10mmo l:10mmo l:5mmo l:20mL:2mmol.
[0042] The molar ratio of the monohydrogen-terminated polysiloxane and allyl alcohol glycidyl ether described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of the monohydrogen-terminated polysiloxane, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 2.4:2:3, and the molar ratio of the diamine-terminated polysiloxane and the modifier is 1:4.
[0043] The molar ratio of the functionalized polysiloxane, triethylamine and acryloyl chloride described in step B3 is 1:4.1:4, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and vinyl polysiloxane is 3g:1.5g:20mL:50mL:2g.
[0044] Embodiment 3: A method for preparing a low creep PP composite material for buckles, comprising the following steps:
[0045] Step A1: dispersing carbon nanotubes in ethanol, stirring and adding 3-mercaptopropyltrimethoxysilane and deionized water at a speed of 300 r / min and a temperature of 70° C., and reacting for 5 hours to obtain functionalized carbon nanotubes; mixing the functionalized carbon nanotubes, 4-vinylbenzaldehyde, benzophenone and toluene uniformly, and reacting for 30 minutes under 365 nm ultraviolet light irradiation to obtain modified carbon nanotubes;
[0046] Step A2: Weigh the following raw materials in parts by weight: 120 parts of PP masterbatch, 10 parts of modified additives, 8 parts of modified carbon nanotubes, 0.8 parts of diisopropyl peroxide and 0.3 parts of tetraisopropyl titanate, add the PP masterbatch, modified additives and diisopropyl peroxide into an internal mixer, melt blend for 10 minutes at a speed of 50 r / min and a temperature of 195°C, then add the modified carbon nanotubes and tetraisopropyl titanate, and melt blend for 30 minutes to obtain a low creep PP composite material for buckles.
[0047] The amount of 3-mercaptopropyltrimethoxysilane used in step A1 is 3% of the mass of the carbon nanotubes, the molar ratio of the mercapto groups on the functionalized carbon nanotubes to 4-vinylbenzaldehyde is 1:1, and the amount of benzophenone used is 1% of the mass of 4-vinylbenzaldehyde.
[0048] The model of the PP masterbatch described in step A2 is HP501M.
[0049] The modified additive is prepared by the following steps:
[0050] Step B1: Tetramethyltetrasiloxane, p-nitrostyrene, chloroplatinic acid and DMF are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 80° C. for 5 hours to obtain a modified monomer; trimethylsilane, n-butyl lithium and hexane are mixed evenly, and nitrogen is introduced for protection, and stirred for 1.5 hours at a speed of 80 r / min and a temperature of 15° C., and the temperature is raised to 50° C., hexamethylcyclotrisiloxane, the modified monomer and tetrahydrofuran are added, and the reaction is carried out for 3 hours, and the temperature is lowered to 25° C., dimethylchlorosilane is added, and the reaction is carried out for 10-15 hours to obtain a monohydrogen-terminated polysiloxane;
[0051] Step B2: uniformly mix monohydrogen-terminated polysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF, and react for 5 hours at a speed of 150 r / min and a temperature of 80° C. to obtain a modifier; uniformly mix octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and react for 3 hours at a speed of 200 r / min and a temperature of 110° C. to obtain a diamine-terminated polysiloxane; uniformly mix the diamine-terminated polysiloxane, the modifier and DMF, and react for 5 hours at a speed of 300 r / min, a temperature of 40° C. and a pH of 12 to obtain a functionalized polysiloxane;
[0052] Step B3: Mix the functionalized polysiloxane, triethylamine and DMF evenly, stir and add acryloyl chloride at a speed of 300 r / min and a temperature of 25°C, and react for 3 hours to obtain vinyl polysiloxane; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add vinyl polysiloxane at a speed of 200 r / min and a temperature of 85°C, and react for 5 hours to obtain a modified additive.
[0053] The molar ratio of tetramethyltetrasiloxane and p-nitrostyrene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrasiloxane, and the amount ratio of trimethylsilane, n-butyl lithium, hexane, hexamethylcyclotrisiloxane, modified monomer, tetrahydrofuran and dimethylchlorosilane is 1mmo l:1mmo l:10mmo l:10mmo l:5mmo l:20mL:2mmol.
[0054] The molar ratio of the monohydrogen-terminated polysiloxane and allyl alcohol glycidyl ether described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of the monohydrogen-terminated polysiloxane, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 2.4:2:3, and the molar ratio of the diamine-terminated polysiloxane and the modifier is 1:4.
[0055] The molar ratio of the functionalized polysiloxane, triethylamine and acryloyl chloride described in step B3 is 1:4.1:4, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and vinyl polysiloxane is 3g:1.5g:20mL:50mL:2g.
[0056] Comparative Example 1: Compared with Example 1, this comparative example uses carbon nanotubes instead of modified carbon nanotubes, and the other steps are the same.
[0057] Comparative Example 2: Compared with Example 1, this comparative example uses propylene oxide instead of the modifier, and the other steps are the same.
[0058] Comparative Example 3. Compared with Example 1, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetrahydrofuran and tetramethyldisiloxane are mixed evenly, and the reaction is carried out for 2 hours at a speed of 150 r / min and a temperature of 105°C to obtain a dihydrogen-terminated polysiloxane. The dihydrogen-terminated polysiloxane, allyl alcohol, chloroplatinic acid and DMF are mixed evenly, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 70°C. The obtained product replaces the functionalized polysiloxane.
[0059] The composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were used to prepare 120 mm × 10 mm × 4 mm specimens according to the standard of GB / T 11546.1-2008. The test temperature was 23°C and the stress was 23 MPa. The creep of the outermost layer of the specimen was recorded after 48 hours. The notched impact strength was tested according to the standard of ISO 179-1:2000. The specimen thickness was 4 mm, the notch was V-notched, the depth was 1 / 3 of the thickness, and the width was 2 mm. The test results are shown in Table 1 below.
[0060] Table 1
[0061]
[0062] It can be seen from the above table that the present application has good anti-creep and impact resistance effects.
[0063] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a low creep PP composite material for buckles, characterized in that: The specific steps include: Step A1: dispersing carbon nanotubes in ethanol, stirring and adding 3-mercaptopropyltrimethoxysilane and deionized water to react to obtain functionalized carbon nanotubes, and uniformly mixing the functionalized carbon nanotubes, 4-vinylbenzaldehyde, benzophenone and toluene, and irradiating with ultraviolet light to react to obtain modified carbon nanotubes; Step A2: Weigh the following raw materials in parts by weight: 100-120 parts of PP masterbatch, 5-10 parts of modified additives, 5-8 parts of modified carbon nanotubes, 0.5-0.8 parts of diisopropyl peroxide and 0.1-0.3 parts of tetraisopropyl titanate, melt-blend the raw materials to obtain a low creep PP composite material for buckles.
2. The method for preparing a low creep PP composite material for buckles according to claim 1, characterized in that: The amount of 3-mercaptopropyltrimethoxysilane used in step A1 is 3% of the mass of the carbon nanotubes, and the molar ratio of the mercapto groups on the functionalized carbon nanotubes to 4-vinylbenzaldehyde is 1:
1.
3. The method for preparing a low creep PP composite material for buckles according to claim 1, characterized in that: The modified additive is prepared by the following steps: Step B1: Tetramethyltetrasiloxane, p-nitrostyrene, chloroplatinic acid and DMF are mixed and reacted to obtain a modified monomer, trimethylsilane, n-butyl lithium and hexane are mixed evenly, nitrogen is introduced for protection, stirring is performed, the temperature is increased and hexamethylcyclotrisiloxane, the modified monomer and tetrahydrofuran are added to react, the temperature is decreased and dimethylchlorosilane is added to react to obtain a monohydrogen-terminated polysiloxane; Step B2: mixing and reacting a monohydrogen-terminated polysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF to obtain a modifier, mixing and reacting octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a diamine-terminated polysiloxane, and mixing and reacting the diamine-terminated polysiloxane, the modifier and DMF to obtain a functionalized polysiloxane; Step B3: functionalized polysiloxane, triethylamine and DMF are mixed and stirred, and acryloyl chloride is added to react to obtain vinyl polysiloxane; zinc powder, ammonium chloride, deionized water and DMF are mixed and stirred, and vinyl polysiloxane is added to react to obtain a modified additive.
4. The method for preparing a low creep PP composite material for buckles according to claim 3, characterized in that: The molar ratio of tetramethyltetrasiloxane and p-nitrostyrene in step B1 is 1:4, and the amount ratio of trimethylsilane, n-butyl lithium, hexane, hexamethylcyclotrisiloxane, modified monomer, tetrahydrofuran and dimethylchlorosilane is 1mmol:1mmol:10mmol:10mmol:5mmol:20mL:2mmol.
5. The method for preparing a low creep PP composite material for buckles according to claim 3, characterized in that: The molar ratio of the monohydrogen-terminated polysiloxane and allyl alcohol glycidyl ether described in step B2 is 1:1, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 2.4:2:3, and the molar ratio of the diamine-terminated polysiloxane and the modifier is 1:
4.
6. The method for preparing a low creep PP composite material for buckles according to claim 3, characterized in that: The molar ratio of the functionalized polysiloxane, triethylamine and acryloyl chloride described in step B3 is 1:4.1:4, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and vinyl polysiloxane is 3g:1.5g:20mL:50mL:2g.
7. A low creep PP composite material for buckles, characterized in that: Prepared according to any one of claims 1 to 6.
Citation Information
Cited By
UV curing printing ink and preparation method thereof
CN120137449A
Corrosion-resistant PE film material and preparation method thereof
CN120310038A